Central Venous Occlusion in End-Stage Renal Failure—A Rare Mimic of Dural Arteriovenous Fistula (DAVF). Issue 1 (June 2021) - Govindappa, Sharath Kumar Goddu; Viswanathan, Lakshminarayanapuram Gopal; Parameshwarappa, Shashidhar Kallappa; Nayak, Naveen; Kumar, Sujit; Pramod, Manithody Narayana-Bhat
Intracerebral hemorrhage is a devastating form of stroke and is more common in patients with hypertension and renal disease. We present the case of a lady suffering from chronic kidney disease who presented with severe headache and aphasia. On evaluation, she was found to have an intraparenchymal hemorrhage in the left temporal lobe with prominent pial and dural veins suggestive of a dural arteriovenous fistula (DAVF). Subsequently, she was detected to have occlusion of the left brachiocephalic vein (LBCV), which resulted in venous hypertension and resulted in this rare complication. Angioplasty followed by stenting of the LBCV resulted in subsidence of her symptoms. We wish to highlight this unusual but treatable complication of limb AV fistula which can mimic intracranial DAVF.